2021
DOI: 10.3389/fmicb.2021.625857
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Soybean Meal Replacement in the Diet of Lactating Holstein Dairy Cows: Modulated Rumen Fermentation and Ruminal Microflora

Abstract: This study was conducted to examine the influences of replacing soybean meal (SBM) with fermented soybean meal (FSBM) in the diet of lactating Holstein cattle on rumen fermentation and ruminal bacterial microbiome. Twenty-four lactating Chinese Holstein dairy cattle were assigned to each of the two treatments in a completely randomized design: the SBM group [the basal total mixed ration (TMR) diet containing 5.77% SBM] and the FSBM group (the experimental TMR diet containing 5.55% FSBM). This trial lasted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 64 publications
7
34
0
Order By: Relevance
“…At the genus level, the microbiota analysis revealed a significant increase in Succiniclasticum and Eubacterium_coprostanoligenes_group in the F group compared to the G and T groups. These genera were positively correlated with elevated concentrations of propionate and butyrate (Li et al, 2021 ; Wang B. et al, 2021 ; Wang Z. et al, 2021 ). Succiniclasticum is a propionate-producing bacterium using succinate (Cao et al, 2020 ), which is the most important precursor of glucose in ruminants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the genus level, the microbiota analysis revealed a significant increase in Succiniclasticum and Eubacterium_coprostanoligenes_group in the F group compared to the G and T groups. These genera were positively correlated with elevated concentrations of propionate and butyrate (Li et al, 2021 ; Wang B. et al, 2021 ; Wang Z. et al, 2021 ). Succiniclasticum is a propionate-producing bacterium using succinate (Cao et al, 2020 ), which is the most important precursor of glucose in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, semi-grazing and barn feeding have become increasingly attractive as alternative strategies to replace traditional grazing. Numerous studies have demonstrated that these alternative feeding patterns improved the growth performance of several famous local sheep breeds (small-tailed Han sheep and Sunit sheep) in Inner Mongolia in China, which resulted in differences in gastrointestinal morphology and intestinal microflora, contributing to the gain of body weight and alternations of other crucial features of ruminants such as health status and even meat quality (Zhang et al, 2014 , 2017 ; Wang B. et al, 2021 ; Wang Z. et al, 2021 ). To date, the underlying regulatory mechanisms for the Gangba sheep response to different feeding patterns have not been well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean meal (SBM) is a highly degradable protein in the rumen and has a balance of highly available amino acids (5,6). Furthermore, SBM is an excellent source of RDP and up to 65% of rumen degradability by rumen microbes (7).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SBM is an excellent source of RDP and up to 65% of rumen degradability by rumen microbes (7). However, the excessive degradability of SBM may not be beneficial to highproducing dairy cows, since it increases urine nitrogen loss (6). Some of the treatment methods to reduce rumen degradability of SBM include extrusion, roasting, or expeller or the addition of lignosulfonate, xylose, or formaldehyde and the use of plant secondary compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These rumen microbes ( Archaea , Bacteria , Protozoa , Fungi , and Viruses ) associate with each other and with their environment. The fermentation activities of these microbes contribute immensely to the health, body maintenance, and production of ruminants through the synthesis of volatile fatty acids (VFAs), vitamins, and microbial protein (MCP) ( Tong et al, 2018 ; Buitenhuis et al, 2019 ; Cunha et al, 2019 ; Wang et al, 2021 ; Wu et al, 2021 ). Furthermore, the disparity in the diversity and abundance of these rumen microbes is known to affect milk yield and milk protein yield in dairy cows ( Tong et al, 2018 ; Xue et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%